Tatak Pilipino [episode no. 62]. (Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Baseball during the 1950's (5 min.) -- Golden era of Philippine movies (20 min.) -- Ramon Magsaysay (20 min.) -- Dress fashion 1950's of Rod Reyes (5 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Reyes, Rod; Magsaysay, Ramon; Baseball -- Philippines; Motion Pictures -- Philippines; Costume design -- Philippines